Evaluation and Investigation of Metal Hydrogen Creation - Popalzai, Raihanah (Journal of Natural Sciences – Kabul University, 2020)
This paper presents a study of the challenges in producing metallic hydrogen and its potential uses. Scientists have been attempting to create metallic hydrogen for decades, but no one has yet managed to provide incontrovertible evidence of success. In 2012, scientists predicted that a new type of high-pressure test chamber could be used to compress hydrogen to 51 GPa, potentially transforming it into the fabled metallic hydrogen. This research could advance planetary science and lead to the development of new materials. It is believed that metallic hydrogen possesses superconducting properties at room temperature and is metastable (meaning it would retain its solid form when brought back to normal pressure). Under normal conditions (without high pressure), the energy between conductive lines and the hydrogen's capacity is 11 electron volts. However, when high pressure is applied, the molecules compress, and the energy decreases to 0.9 electron volts, causing the gas to become metallic. Scientists believe that metallic hydrogen could be used as fuel or as a source of chemical energy for rockets.